Analysis of the Genetic Diversity of Crops and Associated Microbiota - Antonio M. De Ron; Ana Paula Rodiño (Agronomy, 2023)
Plant genetic resources are the basis for genetic improvements in cultivated plants and in future food and feed security [...]